Role of stereotactic radiosurgery for the treatment of brain metastasis in the era of immunotherapy: A systematic review on current evidences and predicting factors. (September 2021) - Gagliardi, Filippo; De Domenico, Pierfrancesco; Snider, Silvia; Roncelli, Francesca; Pompeo, Edoardo; Barzaghi, Lina Raffaella; Bulotta, Alessandra; Gregorc, Vanesa; Lazzari, Chiara; Cascinu, Stefano; Finocchiaro, Gaetano; Mortini, Pietro
Graphical abstract: Highlights: SRS and IT are increasingly used in melanoma and non-small cell lung cancer (NSCLC) brain metastases (BM). A systematic review on current evidences up to December 2020 was performed. SRS-IT combination resulted in a significant improvement in survival and lesion response. SRS-IT combination did not lead to increase in radionecrosis, hemorrhage or other complications. SRS-IT combination is safe and effective in providing a significant improvement in relevant clinical and radiological outcomes. Abstract: Stereotactic radiosurgery (SRS) in combination with immunotherapy (IT) is increasingly used in the setting of melanoma and non-small cell lung cancer (NSCLC) brain metastases (BM). The synergistic properties of this treatment combination are still not deeply understood. IT-SRS appropriate combination has been envisioned as a strategic point in patients' management. Authors performed a systematic review on current evidences up to December 2020. The impact of SRS-IT and different IT schedules on survival, local/distant intracranial control and toxicity, as well as predictive factors for relevant oncological and radiological outcomes has been analyzed. Authors retrieved 23 pertinent studies. Combining SRS with IT resulted in a significant improvement in OS and lesion response with no increase in radionecrosis, hemorrhage or other complications. The present review suggests that combining IT to SRS is safe and effective in providing a significant improvement in relevant clinical and radiological outcomes in melanoma and NSCLC BMs patients.